Analisis Efektivitas Perawatan Pencegahan pada Mesin Simplex di PT. XYZ - Wibowo, Priyo Ari; Rosmalia, Adinda (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to evaluate the effectiveness of preventive maintenance on Simplex machines at PT. XYZ using the Overall Equipment Effectiveness (OEE) method, which is calculated based on three main indicators: availability, performance, and quality. The calculation results show that the OEE value of Simplex machines reached 79%, which is still below the international standard. According to the Six Big Losses analysis, equipment failure, idling, and minor stoppages are the main causes of low machine effectiveness. To achieve this goal, a root cause analysis was conducted using a fishbone diagram. Furthermore, as a strategy to increase machine productivity and preventive maintenance effectiveness, a 5W+1H approach was proposed.